Three new species of Kerria (Hemiptera: Sternorrhyncha: Coccoidea: Tachardiidae), a redesciption of K. yunnanensis Ou & Hong, and a revised key to species of Kerria - Ahmad, Ayashaa; Sharma, K. K.; Ramamurthy, V. V.; Vidyarthi, A. S.; Ramani, R. (Zootaxa, 2013)
Three new species of lac insect, Kerria Targioni-Tozzetti viz., Kerria manipurensis Ahmad & Ramamurthy sp. nov., Kerria maduraiensis Ahmad & Ramamurthy sp. nov., and Kerria thrissurensis Ahmad & Ramamurthy sp. nov. are described and illustrated. Kerria yunnanensis Ou & Hong is illustrated and redescribed, and a key to the known species of Kerria is provided. The usefulness of star pores as a diagnostic character in the subgeneric divisions of Kerria is also discussed.